Outcome of patients with platelet-derived growth factor receptor alpha-mutated gastrointestinal stromal tumors in the tyrosine kinase inhibitor era - Cassier, Philippe A.; Hohenberger, Peter (Clinical cancer research, 2012)
Purpose: Platelet-derived growth factor receptor-alpha (PDGFRA) mutations are found in approximately 5% to 7% of advanced gastrointestinal stromal tumors (GIST). We sought to extensively assess the activity of imatinib in this subgroup. Experimental Design: We conducted an international survey among GIST referral centers to collect clinical data on patients with advanced PDGFRA-mutant GISTs treated with imatinib for advanced disease. Results: Fifty-eight patients were included, 34 were male (59%), and median age at treatment initiation was 61 (range, 19-83) years. The primary tumor was gastric in 40 cases (69%). Thirty-two patients (55%) had PDGFRA-D842V substitutions whereas 17 (29%) had mutations affecting other codons of exon 18, and nine patients (16%) had mutation in other exons. Fifty-seven patients were evaluable for response, two (4%) had a complete response, eight (14%) had a partial response, and 23 (40%) had stable disease. None of 31 evaluable patients with D842V substitution had a response, whereas 21 of 31 (68%) had progression as their best response. Median progression-free survival was 2.8 [95% confidence interval (CI), 2.6-3.2] months for patients with D842V substitution and 28.5 months (95% CI, 5.4-51.6) for patients with other PDGFRA mutations. With 46 months of follow-up, median overall survival was 14.7 months for patients with D842V substitutions and was not reached for patients with non-D842V mutations. Conclusions: This study is the largest reported to date on patients with advanced PDGFRA-mutant GISTs treated with imatinib. Our data confirm that imatinib has little efficacy in the subgroup of patients with D842V substitution in exon 18, whereas other mutations appear to be sensitive to imatinib.